Malaria. - Ashley, E; Mcgready, R; Proux, S; Nosten, F (2006)
Malaria is increasing worldwide due to the emergence and spread of drug resistant strains. This poses major health and economic problems for the population living in endemic areas and increases the risk of infections in travelers. The diagnosis of malaria relies on a biological proof of infection by microscopy or with a rapid test. The treatment must be initiated without delay preferably with an artemisinin containing regimen. Uncomplicated malaria can be treated with oral drugs while severe infections will be hospitalized and treated with injectables. Special attention will be given to the most susceptible groups: children and pregnant women.